Opinions of Stakeholders on the Qualities and Identities of Novice Nurses Graduated from Boromarajonani College of Nursing, Nakhon Ratchasima in the Academic Year 2018 - คงขุนทด ปัทมาภรณ์; จารุพิสิฐไพบูลย์ ฉัตรทอง; แก้วกุลฑล นุชมาศ; เปรมาสวัสดิ์ นฤมล; พางาม มยุรี (Journal of Health Science of Thailand, 2020)
This descriptive research aimed to examine the opinions and correlation of stakeholders on the qualities of nurse graduates according to the Thai Qualifications Framework for Higher Education (TQF) and identities of novice nurses graduated from Boromarajonani College of Nursing, Nakhon Ratchasima in the academic year of 2018. The informants consisted of 152 stakeholders working with novice nurses in the same hospitals. The instruments used to collect the data were questionnaires developed by the researchers. The content validity of the instruments was 0.95, and reliabilities of TQF and identity questionnaires were 0.97 and 0.94, respective. Data were analyzed by using frequency, percentage, mean, standard deviation, and Pearson’s product moment correlation coefficient. The results showed that the overall mean score of quality based on the Thai Qualifications Framework for Higher Education was at high level (mean=4.12, SD=0.52). The highest score of quality was on ethics and moral aspect (mean=4.15, SD=0.63). The lowest score was on analytical thinking (mean=4.07, SD=0.55). The overall mean score on identity was also at high level (mean=4.08, SD=0.64). The highest score of identity was on discipline (mean=4.18, SD=0.64); whereas the lowest scores were on work practice (mean=3.99, SD=0.77) and bringing ultimate benefits to communities (mean=3.99, SD=0.77). There was a high positive relationship between the qualities of novice nurses and their identities (r=0.875, p=0.01). Moreover, the GPA was positively related to the qualities of novice nurses and identities (r=0.267, p=0.01; r=0.258, p=0.01, respectively).